IMPACT OF HIGH TEMPERATURE ON WHEAT (TRITICUM AESTIVUM) CROP - REVIEW - Singh, Harjinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Wheat (Triticum aestivum L.) is one of the most important staple crops in the world. However, rising global temperatures due to climate change have a significant effect on wheat productivity. Wheat is a temperate cereal crop, particularly sensitive to heat stress during key developmental stages, including germination, flowering, and grain filling. Elevated temperatures impair physiological and reproductive processes, leading to reductions in seed germination, tillering, pollen viability, and grain filling duration. Studies indicate that temperatures exceeding optimal thresholds (particularly above 30–32°C) significantly reduce kernel number and weight, spikelet fertility, and ultimately yield. High temperatures disrupt photosynthesis by damaging chlorophyll and carotenoid content and reducing grain quality by affecting starch and protein synthesis. Understanding genotype-specific responses and mechanisms of heat stress tolerance is essential for developing climate-resilient wheat varieties. This review synthesizes the effects of high temperature on wheatgrowth stages, yield traits, and offering insights into breeding strategies.